TINGKAT PEMANFAATAN E-LEARNING MAHASISWA UNIVERSITAS TERBUKA - Julaeha, Siti; Padmo, Dewi (MAJALAH ILMIAH PEMBELAJARAN, 2007)
The study was aimed at getting information about the use of elearning by UT's students in their learning process. Specifically, the study was conducted in order to collect information about factors that encouraged students to use Internet and the problems that students faced in using Internet in their learning process. The population of this study was UT's students who registered courses with flnline learning resourres. The sample was selected by a purposive random sampling techuique with the criteria: UT's students from four faculties and a fJOstwaduate school and courses that were registered by many students. Data collected were descriptively analyzed The results of the study showed that f'1ctors encouraging students to use Internet in their learning process are the flexibility of use of time for learning, the multiuse of Internet: for learning and for doing works; and the speed of getting information. Even though, the students faced problems in using Iniernet for their learning process, such as geographical condition, the bad connection of Internet, financial problem, the leek of facility (the provision of computer), the lack of given information about Internet, and the lack of skills in using Internet.